(untitled) - Lucas, Peter W. (Cambridge, UK,New York, 2004)
This book offers an innovative alternative to the assumption that teeth merely crush, cut, shear or grind food, and demonstrates how teeth adapt to diet. Peter Lucas reveals how tooth form from the earliest mammals to humans can be understood using basic considerations about how different foods fracture. He outlines his theory step-by-step, providing an allometric analysis explaining the factors governing tooth shape and size. An easy-to-use appendix also provides basic mechanics, and methods of measurement. This volume will be essential reading for physical anthropologists and dental and food scientists.
Keywords: Teeth,Teeth,Teeth,Dental anthropology; Evolution,Anatomy